STRICT BUDGET CONTROL ON THE GOVERNMENT OF THE CITY OF SEMARANG IN FACING BUDGET TURBULENCE - Festi Zulfaturrohmah; Julius Pungky Wasono Widagdo; Kris Brantas Abiprayu; Dheasey Amboningtyas (Scholar Express Journals, 2022)
This study aims to provide recommendations regarding the level of tightness / flexibility of budget control applied to the Semarang city government, so that budget deficits or surpluses can be avoided and budget performance increases. Data were obtained through multiple methods, namely surveys with questionnaires and observations and verification of budget archive data and budget realization reports as well as macroeconomic data from the Central Bureau of Statistics of the Semarang City Government. In addition, analyze the data quantitatively and qualitatively. There are three objectives to be achieved in this research, namely 1) Knowing whether Tight Budget Control has an effect on budget deviation, 2) Knowing whether Tight Budget Control requires policies for its implementation, and 3) Knowing how closely related Tight Budget Control is with budget turbulence . The population in this research is the Semarang City Government. The sample was determined purposively, based on the Klassen typology area mapping. The data were tested to estimate the measurement model and structural model, using the Partial Least Square (PLS) method, and testing the interaction effect with Ordinary Least Square (OLS) Regression. The results of this study can be used to anticipate the occurrence of contingency factors in the form of budget turbulence in ensuring budgeting effectiveness, especially when this budget turbulence affects the relationship between tight budget control and budget deviations. And, the benefit to UNNES is that, with this research, a university also requires tight budget control in the form of an institution so that budget turbulence does not occur, even though there is a Strategic Plan and Renop.
Keywords: Strategic; effectiveness; requires; institution